Binahong (Anredera cordifolia (Tenore) Steen.) Leaf Extract Modulates Fatty Acids and Amino Acids to Lower Blood Glucose in High-Fat Diet-Induced Diabetes Mellitus Rats - Dwitiyanti Dwitiyanti; Yahdiana Harahap; Berna Elya; Anton Bahtiar (Advances in Pharmacological and Pharmaceutical Sciences)
Patients with diabetes are 1.6 times more likely to use complementary alternative medicine than nondiabetic patients. Previous studies have shown that Anredera cordifolia (Tenore) Steen. (A. cordifolia) leaf extract has the capacity to lower blood glucose, but the actual mechanisms are unclear. Therefore, in this study, we explored the effect of A. cordifolia leaf extract on the metabolism of fatty acids and amino acids. Six-week-old male Wistar rats were randomly divided into six experimental groups (n = 5 per group). Two groups were fed with a regular diet or a high-fat diet (HFD) for six weeks. The regular diet and HFD groups were administered with 0.5% carboxymethylcellulose as a vehicle, and HFD rats were also fed with a suspension of glibenclamide (0.51 mg/kg body weight (BW)) or A. cordifolia leaf extract (25, 50, and 100 mg/kg BW). During the whole treatment, BW and food intake were recorded weekly. The rats were euthanized seven weeks after treatment. Blood glucose was evaluated by spectrophotometry, while fatty acids and amino acids were evaluated using a gas chromatography/flame ionization detector (GC/FID). All doses of A. cordifolia administration reduced blood glucose significantly, and 50 mg/kg BW was most effective in lowering blood glucose, similar to the effects of glibenclamide. A. cordifolia leaf extract affected the levels of medium-chain fatty acids, especially at 50 mg/kg BW. In contrast, glibenclamide affected long-chain fatty acids (LCFAs) to lower blood glucose. Based on the analysis conducted, we conclude that administration of A. cordifolia leaf extract can decrease blood glucose levels by regulating fatty acid metabolism and that a dose of 50 mg/kg BW in rats was the optimal dose.